Symptoms, adverse events, and outcomes in the use of medicinal cannabis in children and adolescents with autism spectrum disorder: a scoping review protocol. Issue 5 (7th May 2021) - Fletcher, Sarah; Pawliuk, Colleen; Ip, Angie; Oberlander, Tim; Siden, Harold
ABSTRACT: Objective: The objective of this scoping review is to map and identify the symptoms, adverse events, and outcomes in the use of medicinal cannabis in children and adolescents with autism spectrum disorder. Introduction: Autism spectrum disorder is a neurodevelopmental disorder that impacts social communication and social interaction, and is associated with restrictive and repetitive behaviors and interests. Medicinal cannabis has become a potential area of interest for parents for the treatment of autism spectrum disorder symptoms in their children. There is some evidence that cannabinoids may be involved in autism spectrum disorder, laying a potential foundation for medicinal cannabis utility; however, previous reviews did not identify any clinical research on this topic. Inclusion criteria: This scoping review will consider all published and unpublished studies that investigate the use of medicinal cannabis in autism spectrum disorder, where at least 50% of the participants have a diagnosis of autism spectrum disorder and at least 50% of the study population is 0 to 18 years of age, or where pediatric data are reported separately. Studies undertaken in any context (hospital or community) and in any geographic location will be included. Methods: We will search MEDLINE, Embase, CINAHL, PsycINFO, Web of Science, and Google Scholar, and the gray literature sources for studies. Two independent team members will screen titles and abstracts, review full texts for potential inclusion, and extract data for all studies. The results will be presented as a narrative synthesis and in tabular form.